INTERNATIONAL EXPERIENCE OF THE PROSECUTOR’S OFFICE ORGANIZATION - Банах, Сергій Володимирович (The Journal of V. N. Karazin Kharkiv National University. Series Law, 2020)
ANNOTATION. Problematic aspects of defining the tasks and place of the prosecutor’s office, as well as the foreign strategy of improving the organization of the prosecutor’s office are highlighted. The experience of foreign countries of the developed democracy, concerning the work of the prosecutor’s office for its implementation in the legislation of Ukraine, the history of its origin and its modern purpose are analyzed. On the basis of a comparative study of foreign prosecutor’s offices data on their place in the system of government, type of model and basic functions are given, which gives an idea of the role and directions of development of the prosecutor’s office in the leading countries of the modern world. It is stated that the modern Prosecutor’s Office of France is referred to the executive branch of power and reports to the Ministry of Justice. Prosecutors are very close to the judge’s corps because they receive the same training and often move from prosecutors to judges and vice versa throughout their careers. In Germany, prosecuting authorities operate at the general courts of all levels. The Attorney General of the Federal Republic of Germany exercises his authority under the general authority of the Minister of Justice of Germany. According to a special law that defines the legal status of the Prosecutor’s Office in Latvia, the prosecutor’s office is a judicial authority that independently supervises compliance with the law within the established competence. In the UK, there is no public prosecutor’s office or its direct analogue. The Public Prosecutor’s Office operates within the system of public authorities as an independent authority, coordinated by the General Atorney. In the Republic of Lithuania, prosecutors organize and manage the pre-trial investigation process, as well as support state prosecutions in criminal cases. The author summarizes that there is no uniform standard in Europe for the prosecutor’s model. The prosecutor’s models analyzed have advantages and disadvantages, but none of them excludes or prefers one or the other model. Recommendations on improving the Prosecutor’s Office of Ukraine have been provided. KEY WORDS: prosecutor’s office, organization of the prosecutor’s office, international experience, model of the prosecutor’s office, place of the prosecutor’s office, prosecutor, powers of the prosecutor.